Odpowiedź :
Odpowiedź:
[tex]\dfrac{1}{4}-1\dfrac{1}{2}+2\dfrac{3}{5}-5=\dfrac{1}{4}+2\dfrac{3}{5}-1\dfrac{1}{2}-5=\dfrac{1\cdot5}{4\cdot5}+2\dfrac{3\cdot4}{5\cdot4}-6\dfrac{1}{2}=\\\\\\=\dfrac{5}{20}+2\dfrac{12}{20}-6\dfrac{1\cdot10}{2\cdot10}=2\dfrac{17}{20}-6\dfrac{10}{20}=-(6\dfrac{10}{20}-2\dfrac{17}{20})=-(5\dfrac{30}{20}-2\dfrac{17}{20})=\boxed{-3\dfrac{13}{20}}[/tex]
Odpowiedź:
a)
1/4 - 1 1/2 + 2 2/3 - 5 = 1/4 - 1 2/4 - 2 1/3 = -1 1/4 - 2 1/3 = -1 3/12 - 2 4/12 =
= -3 7/12
jesli dodajesz lub odejmujesz ulamki zwykle, musisz zawsze doprowadzic je do wspolnego mianownika
Szczegółowe wyjaśnienie: